Niemożliwość egzystencji autentycznej w świecie patriarchalnym w opowiadaniu Katherine Mansfield "Frau Brechenmacher idzie na wesele" = Impossibility of authentic existence in a patriarchal world in Katherine Mansfield`s "Frau Brechenmacher attends a wedding" - Kubasiewicz, Mirosława (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Katherine Mansfield, a New Zealand author who associated her short adult life with England, is well known for her short stories in which she shows "slices of life" of women of various ages and social positions. Mansfield was aware that women`s freedom to realise their individual potential in a patriarchal world was greatly limited by gender roles imposed on them by tradition.
Keywords: Mansfield, Katherine (pseud.); Mansfield Murry, Kathleen (1888-1923); patriarchal society; public opinion; inauthentic existence; gossip; averageness; społeczeństwo patriarchalne; opinia publiczna; nieautentyczne istnienie; plotka; przeciętność